SUSTAINABILITY OF HOUSEHOLDSâ SEAFOOD PROCESSING ACTIVITIES IN MEKONG DELTA - Nguyen, Xuan Minh; Tran, Quoc Trung (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Seafood processing industry including companies and households accounts for 35% of Mekong deltaâs total agriculturalÂ output. The former mainly concentrates on exports; their processing activities are required and supervised to meet manycriteria of sustainable development and corporate social responsibility by foreign importers. Meanwhile, the latterâsÂ production is for the local market; its processing activities mainly rely on experience and surrounding environment.This study focuses on sustainability of householdsâ seafood processing activities with three pillars including economic,Â social and environmental ones. The research sample of 300 households was collected in 6 provinces of Mekong deltaincluding Ben Tre, Ca Mau, Tien Giang, Dong Thap, Tra Vinh, Bac Lieu in July 2014. Research findings show thatÂ from the economic perspective, physical facilities are outdated; revenues and profits are not stable and household havemore difficulties in collecting materials, obtaining loans for their business and selling their products. In addition, fromÂ social perspective, the average income for seasonal workers is at low levels with 60% paid from 50 - 80 thousands VNDper day and 70% of surveyed households have members and seasonal workers suffering from syndromes of work-relatedÂ diseases including sinusitis, rheumatism, dermatology, eye itching. Moreover, the environment surrounding seafoodÂ processing households is seriously polluted with 71% of households discharging untreated wastewater into nearby seas,Â rivers and canals and disposing solid wastes around their houses. Therefore, 80% of households fail to control and killÂ insects such as flies and bluebottles in their processing area, especially up to 50% failing to know the origins of anti-insectÂ chemistries used. Based on these findings, this paper delivers implications and recommendations for the local governmentÂ and households to improve the sustainability of householdsâ seafood processing activities in Mekong delta.